2021
DOI: 10.1088/1361-6463/ac3034
|View full text |Cite
|
Sign up to set email alerts
|

A review of perfect absorbers based on the two dimensional materials in the visible and near-infrared regimes

Abstract: Two-dimensional (2D) materials, due to their unique electronic, optical and structural properties, have attracted extensive attention of researchers in the world. However, most of 2D materials have low optical absorption efficiencies in the visible and near-infrared regimes, which leads to the weak light–matter interaction and limits their further applications in optoelectronic devices. Thus, enhancing the light–matter interaction of various 2D materials in the visible and near-infrared regimes, has been a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 130 publications
0
22
0
Order By: Relevance
“…At this point, it has worth mentioning that compared with the metamaterial-based MoS 2 absorbers which are mostly consist of complicated three dimensional unit cells 51 53 , without loss of efficiency or bandwidth, our proposed absorber has a two-dimensional design with easy-to-fabricate unit cell.…”
Section: Absorption Enhancement By Inclined Gold Gratingsmentioning
confidence: 99%
“…At this point, it has worth mentioning that compared with the metamaterial-based MoS 2 absorbers which are mostly consist of complicated three dimensional unit cells 51 53 , without loss of efficiency or bandwidth, our proposed absorber has a two-dimensional design with easy-to-fabricate unit cell.…”
Section: Absorption Enhancement By Inclined Gold Gratingsmentioning
confidence: 99%
“…The first metamaterial absorber with unique absorption properties was proposed in 2008, 11 achieving a peak absorption of more than 88% at 11.5 GHz. Subsequently, various metamaterial absorbers 12 , 13 have been designed by adjusting the shapes or components of the metamaterial. The dual band, 14 , 15 triple band, 16 , 17 multi band, 18 , 19 broadband, 20 , 21 and tunable absorption 22 , 23 can gradually be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials made of graphene also benefit from dynamic modulation, which modifies the graphene’s Fermi levels by varying the externally supplied bias voltage to induce various visual phenomena. In optical devices, including electro-optical switches [ 11 , 12 , 13 , 14 ], optical modulators [ 15 , 16 ], optical absorbers [ 17 , 18 , 19 , 20 , 21 ], slow light devices [ 22 , 23 ], and various sensors [ 24 , 25 , 26 ], graphene is widely used in these applications. Luo et al, reported a review on the research progress of 2D material-based absorbing materials in visible and near-infrared light, focusing on the preparation of several typical ideal absorbing materials, such as narrowband, dualband, and broadband, and the related physical mechanisms [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In optical devices, including electro-optical switches [ 11 , 12 , 13 , 14 ], optical modulators [ 15 , 16 ], optical absorbers [ 17 , 18 , 19 , 20 , 21 ], slow light devices [ 22 , 23 ], and various sensors [ 24 , 25 , 26 ], graphene is widely used in these applications. Luo et al, reported a review on the research progress of 2D material-based absorbing materials in visible and near-infrared light, focusing on the preparation of several typical ideal absorbing materials, such as narrowband, dualband, and broadband, and the related physical mechanisms [ 21 ]. This can help researchers to better understand 2D material-based absorbing materials in the visible and near-infrared regions.…”
Section: Introductionmentioning
confidence: 99%